2001
DOI: 10.1161/hc37t1.094930
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Nitric Oxide Release and Endothelium-Derived Hyperpolarizing Factor–Mediated Hyperpolarization Between Human Radial and Internal Mammary Arteries

Abstract: Background-Arterial grafts for CABG have been used increasingly, and the radial artery (RA) has become a preferable graft, secondary to the internal mammary artery (IMA). In the present study, we investigated and compared NO release and endothelium-derived hyperpolarizing factor (EDHF)-mediated hyperpolarization for IMA and RA. Methods and Results-IMA and RA segments taken from CABG patients were placed in an organ chamber. An NO-sensitive electrode (to directly measure NO release) or intracellular glass micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(88 citation statements)
references
References 24 publications
3
84
0
1
Order By: Relevance
“…Other studies suggest that the endothelial function of radial artery is similar to that of the IMA (25,26). However, other investigators have reported differences in endothelium-derived NO release and hyperpolarizing factor in the IMA and radial artery (27,28 This has led researchers to look for experimental models for functional experiments in an attempt to avoid the detrimental impact of these cardiovascular risk factors on vasoreactivity. Recently, we addressed the neurogenic contractions produced in porcine radial artery using a combined histological/functional approach (4).…”
Section: +mentioning
confidence: 99%
“…Other studies suggest that the endothelial function of radial artery is similar to that of the IMA (25,26). However, other investigators have reported differences in endothelium-derived NO release and hyperpolarizing factor in the IMA and radial artery (27,28 This has led researchers to look for experimental models for functional experiments in an attempt to avoid the detrimental impact of these cardiovascular risk factors on vasoreactivity. Recently, we addressed the neurogenic contractions produced in porcine radial artery using a combined histological/functional approach (4).…”
Section: +mentioning
confidence: 99%
“…ITA grafts promote a greater release of nitric oxide than radial artery (RA) and saphenous vein (SF) grafts [13]. This makes the ITA a 'live graft' capable of dilation (adaptation of the caliber) and consequent increase in the blood flow, responding to the demand of the coronary territory and the area of the myocardium supplied.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that the lower capacity of nitric oxide release may contribute to the susceptibility of RA to the vasospasm and may have an impact on the long-term patency [56].…”
Section: Cabg Using Radial Artery Graftmentioning
confidence: 99%